Arborização urbana como um mecanismo de pagamento por serviços ambientais (PSA) no município de Rio Claro, SP - Minigildo, Débora Gisele [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Environmental services (ES) are provided by ecosystems and are defined as a product of relationships between biotic and abiotic components ensuring goods and services to the human being, contributing to their well-being and for the proper functioning of the planet. The Payments for Environmental Services (PES) is a public policy to compensate, monetary or otherwise, the human actions aiming at recovery, maintenance and conservation of ecosystems. Most of existent PES-scheme is implemented in the rural area, although its implementation in the urban area - where the majority of current Brazilian population lives - could minimize the negative impacts on the environment, resulting from the excessive urban growth and the intensive natural resources exploration. In this context, urban forestry stands out as a possible action on a PES-scheme to be implemented in the urban environment, since it is able to provide relevant ecosystem services described in the table CICES (Common International Classification of Ecosystem Services), such as regulation, maintenance and cultural services. Due to the importance of a urban PES using the urban forestry as a possible action to provide some ES, this research aims: (i) to access the benefits from this PES-scheme to Rio Claro municipality, SP State, focusing on the afforestation; (ii) investigate the afforestation index (IAUrb) and the deficit of trees in the city and (iii) to evaluate the economic feasibility of implementing a PSA program using the afforestation as a service performed by the citizens, who could be benefit with a reduction in the IPTU tax. The IAUrb was calculated by the number of trees per linear kilometer of sidewalk, considering the ideal as 12m spacing between the trees. The economic feasibility was assessed by using the forecast revenue of residential tax, the costs estimation of acquiring the trees, in addition to estimating the number of accessions...

Os serviços ambientais são aqueles prestados pelos ecossistemas como produto das relações entre os seus componentes bióticos e abióticos, que garantem bens e serviços ao ser humano, contribuindo para seu bem-estar e para o bom funcionamento do planeta. O Pagamentos por Serviços Ambientais (PSA) é uma medida pública definida como a compensação, monetária ou não, às ações humanas direcionadas à recuperação, manutenção e conservação dos ecossistemas provedores de serviços ambientais. Os sistemas de PSA existentes são em sua grande maioria voltados às áreas rurais, no entanto, sua implementação na área urbana (local onde a maior parte da população brasileira atual vive) permite minimizar os impactos ambientais provenientes do demasiado crescimento urbano, associado à intensa exploração dos recursos naturais. Nesse contexto, a arborização urbana destaca-se como possível ação em um mecanismo de pagamento por serviços ambientais a ser executado no ambiente urbano, já que é capaz de fornecer relevantes serviços descritos na tabela CICES (Classificação Internacional Comum dos Serviços Ecossistêmicos), como serviços de regulação e manutenção e serviços culturais. Dada a importância de um sistema de PSA urbano e da arborização urbana como possível ferramenta, os objetivos deste trabalho foram: (i) avaliar os benefícios advindos de um projeto de PSA urbano, no contexto de Rio Claro, SP, tendo como foco a Arborização; (ii) investigar o índice de arborização, bem como o déficit de árvores na cidade e (iii) avaliar a viabilidade econômica de implantação de um programa de PSA utilizando-se da arborização urbana como serviço executado pelos munícipes, que por sua vez, seriam beneficiados com o abatimento de parte do seu IPTU. O índice de arborização foi obtido pelo número de árvores por quilômetro linear de calçada, sendo recomendado...
Keywords: Ecologia vegetal; Meio ambiente; Arborização das cidades - Rio Claro (SP); Plant ecology